The Use of Code Switching and Code Mixing in the Film Belok Kanan Barcelona (2018) - Shajidah, Khalisyah Hana; Ramadhina, Retno; Indrayanti, Sri (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This study is based on social interaction in a multilingual society where there is code switching and code mixing occurs. The purpose of this research is to find out what are the forms of code switching and code mixing in Belok Kanan Barcelona and the factors that exist in the film Belok Kanan Barcelona. The method used is a qualitative descriptive method which is done by recording all the data that appears in the movie. The material is also analyzed by listening techniques and note-taking techniques. Therefore, in this study the writer uses the movie as the object of code switching and code mixing analysis. Since the story is set in an international country, the movie shows a multilingual situation where the characters communicate in Indonesian, Javanese, Makasarese, English, and Spanish according to the context and situation they face. The results of this study have found 16 data, which is code-switching data as much as 6 data and code-mixing data as much as 10 data.